2015
DOI: 10.4081/ijas.2015.3263
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine and Glutamic Acid Supplementation Enhances Performance of Broiler Chickens Under the Hot and Humid Tropical Condition

Abstract: Day-old (day 1) commercial broiler chickens were fed i) basal diet (control), ii) basal diet +0.5% AminoGut (AG), or iii) basal diet +1% AG from 1 to 42 d of age under the hot and humid tropical environment. AminoGut is a commercial dietary supplement containing a mixture of L-glutamine (Gln) and L-glutamic (Glu) acid. Weight gain and feed conversion ratio during the starter (1 to 21 d) and overall (1 to 42 d) periods improved linearly and quadratically with AG supplementation when compared to control. Supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
3
9
0
8
Order By: Relevance
“…Although it has been shown that Gln has a positive effect in alleviating heat stress, there is little research on the relationship between Gln and HSP70 expression in broilers under high temperature conditions [23]. Therefore, in this study, we determined whether Gln can enhance the anti-oxidative stress ability of the breast muscle by increasing the expression of antioxidant genes and HSP70 in broilers exposed to cyclic heat stress.…”
Section: Introductionmentioning
confidence: 95%
“…Although it has been shown that Gln has a positive effect in alleviating heat stress, there is little research on the relationship between Gln and HSP70 expression in broilers under high temperature conditions [23]. Therefore, in this study, we determined whether Gln can enhance the anti-oxidative stress ability of the breast muscle by increasing the expression of antioxidant genes and HSP70 in broilers exposed to cyclic heat stress.…”
Section: Introductionmentioning
confidence: 95%
“…Glutamine dietary supplementation decreases health problems, prevents intestinal atrophy, maintains antioxidant status, decreases incidence of diarrhea, resulting in increased weight gain and improved efficiency (Haynes et al, 2009;Zhong et al, 2011;Wang et al, 2014;Watford, 2015). Similar results have also been reported in broiler chicken (Nassiri Moghaddam and Alizadeh-Ghamsari, 2013;Jazideh et al, 2014;Nascimento et al, 2014;Manvailer et al, 2015;Muro et al, 2015;Olubodun et al, 2015;Ribeiro Jr et al, 2015;Luquetti et al, 2016;Maiorka et al, 2016;Namroud et al, 2017).…”
Section: Introductionmentioning
confidence: 61%
“…High ambient temperature and high relative humidity (RH) or low RH occurring during the hot-humid or dry season have been shown to cause heat stress in broilers [3,4]. The fast growing commercial broiler chickens are particularly susceptible to heat stress to induce metabolic disorder [5,6,7]. In addition, global warming will further accentuate heat stress related problems.…”
Section: Introductionmentioning
confidence: 99%